RESEARCH OF WATER QUALITY ON SELAKAU RIVER FOR RICE IRRIGATION IN THE SUNGAI NYIRIH VILLAGE SELAKAU SUBDISTRICT OF SAMBAS REGENCY - suherman suherman; Ir.H.Riduansyah, MP Ir.H.Riduansyah, MP (Jurnal Sains Pertanian Equator, 2016)
The river is one of supporting the agricultural activities by human,the river is one of the sources of water that can be used for irrigation in an agricultural activity. The irrigation water is expected to increase the production of food crops in particular, therefore, to determine the suitability of irrigation water requires a water quality testingfor irrigation water. The water quality test will be used to determine the suitability of water that may or may not be managed to perform activities of irrigated agriculture. The purpose of this study is to determine the water quality of the river Selakau as a source of irrigation water the village of Sungai Nyirih Selakau District of Sambas Regency. The research variables are divided into two, namely: the main variable that consists of Salinity / Electrical Conductivity, Sodium Absorption Ratio (SAR), Residual Sodium Carbonate (RSC), Boron and pH. While the supporters Variable are Temperature / Water Temperature (° C) and brightness. Based on observations on Salinity / electrical conductivity, Ratio Absorption Sodium (SAR), Residual Sodium Carbonate (RSC), Boron, pH, Temperature / Water Temperature (° C) and Brightness have fulfilled the criteria of assessment of irrigation water, so the river water Selakau can used as irrigation water rice plants in Sungai nyirih.